Effect of supply voltage variations on single-phase capacitor clamped multilevel inverter fed induction motor drive - Diyoke, Gerald Chidozie; Eya, Candidus Ugwuoke (International Journal of Applied Power Engineering (IJAPE), 2023)
This article presents the effect of supply voltage variations on single-phase capacitor-clamped multilevel inverter-fed induction motor drives. This research is tailored at determining the best torque value and speed to attain a stable state under input voltage variation and minimum time response to realize low percentage harmonic distortions. The effect of constant power quality disturbance harms the performance and behavior of asynchronous motors based on harmonic contents and other energy source integrations. The multilevel inverter has shown good performance in motor drives. This paper deals with the effect of input voltage variations on a single-phase multilevel capacitor-clamped inverter for asynchronous induction motor drives. A five-level capacitor-clamped inverter with an in-phase disposition pulse width modulation technique is adopted. Four high-frequency triangular carrier signals are generated and compared with a reference sinusoidal signal. As a result of this approach, the inverter switches firing signals are generated. The open-loop model is designed and simulated utilizing MATLAB/Simulink and results based on different values of supply voltage are presented. The current and voltage total harmonic distortions (THDs) obtained are 4.97% and 4.46% respectively at the best operating voltage of 400 V and at maximum torque of 47 Nm.